Pola Asuh Orangtua dalam Penanaman Nilai Agama dan Budi Pekerti di KB Uwais al Qorni Desa Sungai Harapan Kabupaten Kampar - Yusmaleni Yusmaleni; Nopa Wilyanita; Herwina Herwina (Darul Yasin Al Sys, 2026)
Although the instillation of religious values and moral character in early childhood has become an important concern in family education, studies that specifically describe parenting patterns in this context remain relevant for further exploration. This study aims to describe parenting patterns in instilling religious values and moral character in early childhood at KB Uwais Al Qorni, Sungai Harapan Village, Kampar Regency. This study used a field research method with a descriptive qualitative approach. The research subjects consisted of six parents of students who were selected purposively. Data were collected through observation, interviews, and documentation, then analyzed using the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. The results showed that parents applied three types of parenting patterns, namely democratic, authoritarian, and permissive. Democratic parenting was the most dominant pattern, characterized by two-way communication, role modeling, habituation of worship, and the application of clear boundaries while still respecting the child’s opinions. Authoritarian and permissive parenting patterns were also found, although they were generally combined with democratic parenting. These findings show that the appropriate application of parenting patterns has a positive effect on the formation of children’s discipline, responsibility, politeness, and worship habits. The conclusion of this study emphasizes the importance of parents’ consistency in applying democratic parenting and the need for good cooperation with the school to strengthen the instillation of religious values and moral character in a sustainable manner.